Chronic Plaque Psoriasis Exacerbated by Telmisartan Therapy: A Case Report - ., Amisha; Malik, Paras; Pathania, Monika; Rathaur, Vyas Kumar (International Journal of Innovative Research in Medical Science, 2019)
Background: Psoriasis is an immune-mediated chronic inflammatory dermatosis with a complex interplay of environmental and genetic factors. Among the various documented triggers, drug-related psoriasis constitutes a distinct entity with exposure resulting in either induction or exacerbation of psoriasis. Here we describe the case of a 45-year-old female with telmisartan aggravated chronic plaque psoriasis previously well controlled on oral methotrexate.